Questioning fairness: the relationship of mental health and psychopathic characteristics with young offenders' perceptions of procedural justice and legitimacy. (13th June 2016) - Penner, Erika K.; Shaffer, Catherine S.; Viljoen, Jodi L.
Abstract: Background: Theories of procedural justice suggest that individuals who experience the criminal justice system as fair are more likely to perceive it as legitimate and, in turn, are less likely to reoffend. However, when individuals come into contact with the legal system, they are not blank slates – they have beliefs and personality characteristics that may systematically influence such perceptions. Aims: Our aim was to establish the extent to which demographic characteristics, legal history and clinical features, including personality characteristics, systematically influenced the degree to which young people experience the justice system as fair and legitimate. Method: Self‐report, file and interview data were collected from ninety‐two 12 to 17‐year‐olds on probation in Western Canada. Results: Substance use and traumatic experiences were inversely correlated with perceptions of procedural justice and legal legitimacy. Young people with higher scores on interpersonal, lifestyle and antisocial facets of the psychopathy checklist: youth version believed less strongly in the legitimacy of the law, but regression analyses confirmed that only history of trauma was independently associated with perceived procedural justice and legitimacy. Those in the youngest age group were more likely to have positive perceptions of justice than older youths, but demographics and legal history otherwise did not relate to outcomes. Conclusions: Our findings suggest that examining the relationship between procedural justice, legitimacy and offending without taking intra‐individual variables into account may neglect important influences on those relationships. Other research has begun to show that young people who do not accept the law as legitimate or the criminal justice system as fair are more likely to offend. Copyright © 2016 John Wiley & Sons, Ltd.